2009
DOI: 10.1074/jbc.m901902200
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of SenP5 from the Nucleoli to the Mitochondria Modulates DRP1-dependent Fission during Mitosis

Abstract: The mechanisms that ensure an equal inheritance of cellular organelles during mitosis are an important area of study in cell biology. For the mitochondria fragment during mitosis, however, the cellular links that signal these changes are largely unknown. We recently identified a SUMO protease, SenP5, that deSUMOylates a number of mitochondrial targets, including the dynamin-related fission GTPase, DRP1. In interphase, SenP5 resides primarily within the nucleoli, in addition to a cytosolic pool. Here we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 50 publications
3
131
0
Order By: Relevance
“…Several studies indicate a close relationship between the rDNA arrays, ribosomal biogenesis and the mitochondria [10][11][12][13] . For instance, recent evidence points to the import of 5S rRNAs into the mitochondria through a highly regulated process 35,36 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies indicate a close relationship between the rDNA arrays, ribosomal biogenesis and the mitochondria [10][11][12][13] . For instance, recent evidence points to the import of 5S rRNAs into the mitochondria through a highly regulated process 35,36 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, recent evidence points to the import of 5S rRNAs into the mitochondria through a highly regulated process 35,36 . Moreover, tight regulation of nuclear transcription ensures proper mitochondrial biogenesis 11,13 . As such, functional crosstalk between the rDNA dosage and the mitochondria might be manifested in natural populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced dynamics accompanies the process of ageing [41], is associated with the development of neurodegenerative diseases [42][43][44] and plays an important role in the execution of apoptosis [45,46]. Repetitive fusion and fission of mitochondria during the cell cycle has to be regulated [47][48][49][50]; otherwise, the continuity of the mitochondrial genome is not properly guaranteed [51,52], resulting in mitochondrial heterogeneity and malfunction [53]. Obviously, mitochondrial dynamics is important for quality control [27,54].…”
Section: The Measurement Of Mitochondrial Dynamics and Its Applicatiomentioning
confidence: 99%
“…Studies of DRP1 post-translational modifications, including phosphorylation and SUMOylation, have yielded insight into the cellular mechanisms that regulate mitochondrial fission in mammals. H. McBride (Ottawa, ON, Canada) and colleagues previously showed that several mitochondrial proteins, including DRP1, are reversibly SUMOylated by the E3 ligase MAPL and the SUMO protease (Harder et al, 2004;Zunino et al, 2007Zunino et al, , 2009Braschi et al, 2009). In a surprising new twist to this story, McBride reported that SenP5 moves from the nucleolus to the mitochondrial surface during the G2/M phase of the cell cycle, where its deSUMOylation activity promotes DRP1 assembly and mitochondrial fission ).…”
Section: Mitochondrial Membrane Fission and Fusionmentioning
confidence: 99%